Seasonal and Differential Sesquiterpene Accumulation in Artemisia annua Suggest Selection Based on Both Artemisinin and Dihydroartemisinic Acid may Increase Artemisinin in planta - Ferreira, Jorge F. S.; Benedito, Vagner A.; Sandhu, Devinder; Marchese, José A.; Liu, Shuoqian (Frontiers in Plant Science, 2018)
Commercial Artemisia annua crops are the sole source of artemisinin (ART) worldwide. Data on seasonal accumulation and peak of sesquiterpenes, especially ART, in commercial A. annua, is lacking, while current breeding programs focus only on ART and plant biomass, but ignores dihydroartemisinic acid (DHAA) and artemisinic acid (AA). Despite past breeding successes, plants richer in ART are needed to decrease prices of artemisinin-combination therapy (ACT). Our results show that sesquiterpene concentrations vary greatly along the growing season and that sesquiterpene profiles differ widely among chemotypes. Field studies with elite Brazilian, Chinese, and Swiss germplasms established that ART peaks in vegetative plants late August to early September, suggesting that ART is related to the photoperiod, not flowering. DHAA peaks with ART in Chinese and Swiss plants, but decreases, as ART increases, in Brazilian plants, while AA remains stable through the season in all genotypes. Chinese plants peaked at 0.9% ART, 1.6% DHAA; Brazilian plants at 0.9% ART, with less than 0.4% DHAA; Swiss plants at 0.8% ART and 1% DHAA. At single-date harvests, seeded Swiss plants produced 0.55-1.2% ART, with plants being higher in DHAA than ART; Brazilian plants produced 0.33-1.5% ART, with most having higher ART than DHAA. Elite germplasms produced from 0.02-0.43% AA, except Sandeman-UK (0.4-1.1% AA). Our data suggest that different chemotypes, high in ART and DHAA, have complementary pathways, while competing with AA. Crossing plants high in ART and DHAA may generate hybrids with higher ART than currently available in commercial germplasms. Selecting for high ART and DHAA (and low AA) can be a valuable approach for future selection and breeding to produce plants more efficient in transforming DHAA into ART in planta and during post-harvest. This novel approach could change the breeding focus of A. annua and other pharmaceutical species that produce more than one desired metabolite in the same pathway. Obtaining natural variants with high ART content will empower countries and farmers who select, improve, and cultivate A. annua as a commercial pharmaceutical crop. This selection approach could enable ART to be produced locally where it is most needed to fight malaria and other parasitic